2017
DOI: 10.1130/l638.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of widespread wildfires in a coal seam from the middle Permian of the North China Basin

Abstract: The North China Basin is the largest coal-bearing basin in China, and has an areal extent of 800,000 km 2 . We analyzed 138 coal samples and in situ pillar coal samples of the middle Permian from this basin by macropetrography, microscope, scanning electron microscope, gas chromatography, and gas chromatography-mass spectrometer in order to study wildfires. High contents of inertinite (charcoal) and natural coke particles observed in coal samples indicate that vegetation in precursor mires and peats of the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…The coals in the western part of the study area contain higher charcoal abundances than those in the eastern part based on the coal petrological evidence (Table 1). Higher levels of inertinite in contemporaneous coals have also been recorded from New Zealand, America, Canada, Africa, and North China (Diessel 2010;Sun et al 2017). The variability in inertinite content indicates that wildfires were prevalent in the coal-forming peatland during the Early Cretaceous, and may record transitional periods from higher wildfire activity (Erlian Basin and Hailar Basin) to lower wildfire activity (Sanjiang Basin).…”
Section: Inertinite Macerals: Wildfire Implicationsmentioning
confidence: 94%
“…The coals in the western part of the study area contain higher charcoal abundances than those in the eastern part based on the coal petrological evidence (Table 1). Higher levels of inertinite in contemporaneous coals have also been recorded from New Zealand, America, Canada, Africa, and North China (Diessel 2010;Sun et al 2017). The variability in inertinite content indicates that wildfires were prevalent in the coal-forming peatland during the Early Cretaceous, and may record transitional periods from higher wildfire activity (Erlian Basin and Hailar Basin) to lower wildfire activity (Sanjiang Basin).…”
Section: Inertinite Macerals: Wildfire Implicationsmentioning
confidence: 94%
“…Coalfield, North China Basin b). Most of the studies of palaeo-wildfires are related to the wildfires occurred in the Late Paleozoic era (Arzadún et al, 2017;Jasper et al, 2013;Kauffmann et al, 2016;Manfroi et al, 2015;Shen et al, 2011;Singh and Shukla, 2004;Sun et al, 2017). These palaeo-wildfires consumed O 2 and released CO, CO 2 to the atmosphere which modified the atmospheric temperatures and ecosystems (Berner, 2006;Lenton, 2013;Scott and Glasspool, 2006;Scott et al, 2016).…”
Section: Wildfire Evidence From the Middle And Late Permian Hanxingmentioning
confidence: 99%
“…These palaeo-wildfires consumed O 2 and released CO, CO 2 to the atmosphere which modified the atmospheric temperatures and ecosystems (Berner, 2006;Lenton, 2013;Scott and Glasspool, 2006;Scott et al, 2016). Sun et al (2017) have reported also that the palaeowildfires of the Middle Permian could have discharged massive quantities of pollutants and increased the ambient temperature, causing the floral extinction that occurred at the Middle Permian. Shen et al (2011) have reported also that the wildfires of the Late Permian may have acted as a catalyst to the Permo-Triassic Boundary (PTB) mass extinction events.…”
Section: Wildfire Evidence From the Middle And Late Permian Hanxingmentioning
confidence: 99%
See 1 more Smart Citation
“…The shale gas source rock formations were mainly a set of dark fine-grained rock masses formed during the Carboniferous and Permian Periods, and contained from bottom to top, the Benxi Formation, Taiyuan Formation, Shanxi Formation, and Shihezi Group (Sun et al, 2002(Sun et al, , 2016(Sun et al, , 2017.…”
Section: Main Formation Of the Fine-grained Rock Massesmentioning
confidence: 99%